2017
DOI: 10.1080/10402004.2016.1272730
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Shear Degradation of Lithium Soap Grease at Ambient Temperature

Abstract: In this article, the shear degradation of lithium 12-hydroxy stearate grease will be measured using an inhouse-developed Couette aging machine. In this device the shear rate is well defined. The aging is related to the generated entropy density as described in Rezasoltani and Khonsari's work (Tribology Letters, Vol. 56, No. 2, pp. 197-204, 2014). The rheological properties of the aged samples were evaluated using a parallel-plate rheometer. The results showed that there are two aging phases with different degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…The current article extends the work that was earlier published in Zhou, et al (13) where the shear degradation was described at a fixed temperature. The influence of temperature on shear degradation will be included in this study.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…The current article extends the work that was earlier published in Zhou, et al (13) where the shear degradation was described at a fixed temperature. The influence of temperature on shear degradation will be included in this study.…”
Section: Introductionsupporting
confidence: 80%
“…The influence of temperature on shear degradation will be included in this study. The results show that elevated temperatures accelerate aging due to the possible change in thickener properties (Salomonsson,et al (4); Couronne, and Vergne (5); Bondi, et al (20)), which is not well described by the entropy concept (Rezasoltani and Khonsari (12); Zhou, et al (13)). It will be shown that grease degradation is determined by the energy density where the Arrhenius equation should be used to include thermal effects, called corrected energy density, E m , here.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting investigations of the structural change inside a grease comes from [4][5][6]. Paszkowski and Olsztynska-Janus [4] investigated the degradation process of Li-soap lubricating greases.…”
Section: Introductionmentioning
confidence: 99%
“…These authors stated that the degree of disintegration of the greases micro-structure depends mainly on the shear rate. Zhou et al [5] made experimental work by using a rheometer. They show a continuous change of thickener structure with a continuous entropy production and differ a non-stationary and a stationary period.…”
Section: Introductionmentioning
confidence: 99%
“…The fibre breakdown is a physical complex process where the fibres are broken in the contact points at low shear rates, while at high shear rates the fibres themselves experience a breakdown in height or length [9]. Another property of greases that adds to the complexity in obtaining reliable models is that the grease is affected by shear degradation [10] during long time of shear exposure. This is coupled to the evolution of the stress in the flow-which in addition to having a nonlinear relation to the shear rate-also is dependent on time, i.e.…”
Section: Introductionmentioning
confidence: 99%